Targeting Oncostatin M Receptor to Attenuate Carotid Artery Plaque Vulnerability in Hypercholesterolemic Microswine - Trinh, Jerry; Shin, Jennifer; Rai, Vikrant; Agrawal, Devendra K (Cardiology and Cardiovascular Medicine, 2024)
Atherosclerosis is a chronic inflammatory disease that leads to acute embolism via the formation of atherosclerotic plaques. Plaque formation is first induced by fatty deposition along the arterial intima. Inflammation, bacterial infection, and the released endotoxins can lead to dysfunction and phenotypic changes of vascular smooth muscle cells (VSMCs), advancing the plaque from stable to unstable form and prone to rupture. Stable plaques are characterized by increased VSMCs and less inflammation while vulnerable plaques develop due to chronic inflammation and less VSMCs. Oncostatin M (OSM), an inflammatory cytokine, plays a role in endothelial cells and VSMC proliferation. This effect of OSM could be modulated by p27KIP1, a cyclin-dependent kinase (CDK) inhibitor. However, the role of OSM in plaque vulnerability has not been investigated. To better understand the role of OSM and its downstream signaling including p27KIP1 in plaque vulnerability, we characterized the previously collected carotid arteries from hyperlipidemic Yucatan microswine using hematoxylin and eosin stain, Movat Pentachrome stain, and gene and protein expression of OSM and p27KIP1 using immunostaining and real-time polymerase chain reaction. OSM and p27KIP1 expression in carotid arteries with angioplasty and treatment with either scrambled peptide or LR12, an inhibitor of triggering receptor expressed on myeloid cell (TREM)-1, were compared between the experimental groups and with contralateral carotid artery. The results of this study elucidated the presence of OSM and p27KIP1 in carotid arteries with plaque and their association with arterial plaque and vulnerability. The findings suggest that targeting OSM and p27KIP1 axis regulating VSMC proliferation may have therapeutic significance to stabilize plaque.